Dinamika Anjuran Dosis Pemupukan N, P, dan K pada Padi Sawah - Ali Jamil; Sarlan Abdulrachman; Mahyuddin Syam (Iptek Tanaman Pangan, 2014)
Until 1960s, farmers planted rice only once in a year, due to the use of late maturing, 5 to 6 month varieties. Fertilizer recommendation rate to optimize productivity of those varieties was low, 20 to 40 kg N/ha. The Green Revolution technology introduced in the late 1960s which was characterized by the use of high-yielding varieties highly responsive to fertilizer, was then adopted in the BIMAS (Mass Intensification Guidance) Program. The successful program in increasing yield of rice was then followed by INMAS (Mass Intensification), INSUS (Special Intensification), and OPSUS (Special Operations) programs, where the more refined fertilizer recommendation rates had played an important role, which subsequently led Indonesia achieved rice selfsufficiency in 1984. The levelling-off of rice production which occurred in the late 1980s was then addressed by introducing SUPRA INSUS program, containing 10- technology components of D-package. The very high rate of fertilizer recommendation on the D-package had worried many parties for its inefficiency and negative effect on the environment. Research was then intensified on the fertilizer use efficiency, especially N fertilizer, including the application of urea super granules (USG), and sulfur coated urea (SCU). Green manures such as Azolla sp and Sesbania rostrata were also being studied as alternative for sources of N nutrient. The P and K nutrient status in the soil was mapped which was used as reference for the fertilizer allocation in each province, based on the map scale of 1: 250,000. The recommendation rate of fertilizer for the sub-district level, was developed based on the map scale of 1: 50,000. To optimize the use of fertilizers, soil test kit and leaf color chart (LCC) were recommended to be used by the extension agents, so that farmers could benefit from the more efficient use of N, P, and K fertilizers. Long-term fertilizer field trials had been conducted since 1970s, where the result had shown that in intensive paddy fields, P and K fertilizers did not need to be applied every season. With the current rapid advanced in technology information, farmers have an access for the recommendation rate of fertilizer for specific location via internet, smart phones, or conventional hand phone. The validation of the fertilizer recommendation, known as site specific nutrient management (SSNM), had been carried out in major rice producing provinces, which proved to give some benefits to farmers, through the use of lower rates of fertilizers but higher yields. SSNM had played an important role in the formulation of integrated crop management (ICM) approach, implemented in the national rice production program. The Expert System of Rice Cultivation (SIPADI) operated by using computer, could be used as a tool in providing recommendation for specific location rice technology package. Adoption of SSNM faces several challenges such as small land holding, of which farmers tend to buy “small quantity” of fertilizer but actually too much for his land. The subsidized fertilizer prices had also discouraged farmers from following the SSNM.